Nasser : Hero of the Arab Nation - Gordon, Joel (London Oneworld Publications, 2009)
To cite an old Egyptian cliche, Nasser (1918-1970) was the ''first Egyptian to rule Egypt since Cleopatra.'' Deposing the corrupt king Farouk, abolishing the monarchy and negotiating the withdrawal of the British, Nasser was truly beloved by millions. Even after catastrophic military disaster in the ''Six-Day War'' of 1967, having resigned in humiliation, such was his standing that people filled the streets to clamor for his reinstatement. In this captivating profile, Joel Gordon examines the legacy of the famous autocrat, being careful to include his limitations as well as his many strengths.
Include Illustration and Index
Keywords: Presidents -- Nasser, Gamal Abdel, 1918-1970 -- Egypt